Bad hare day - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1996)
When Tim Swanson discovers his favorite magician is a total grump, he steals his bag of secret, scary tricks.
"A Parachute Press book"--T.p. verso.
RL 4.
008-012.
Accelerated Reader AR
Keywords: Magicians -- Fiction; Horror tales; Horror fiction